Do Macroeconomic Shocks Affect Intuitive Inflation Forecasting? An Experimental Investigation - Marvin Deversi (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2014)
In an experimental setting impulse-response behaviour in intuitive inflation forecasting is analysed. Participants were asked to forecast future values of inflation for a fictitious economy after receiving charts and lists of past values of inflation and output gap. Thirty periods were forecasted stepwise and feedback on performance was provided after each period. In a between subjects design, participants experienced a negative or positive supply shock. The results suggest that participants barely report rational forecasts. Instead, simple backward-looking rules describe stated forecast series. Forecasting is heterogeneous across agents and over time. Before the shock, most participants can be described by natural expectations. Due to the shocks 69% of participants are found to switch their forecasting rule. After the negative supply shock, subjects increase efficiency of forecasts. But, after a positive supply shock efficiency drops down to zero; this is evidence for a negativity bias. As a main result, macroeconomic shocks do alter the way experimental participants form intuitive inflation forecasts, however, to what extent depends on the shocks' characteristics. – – Die vorliegende Studie untersucht die Effekte makroökonomischer Extremsituationen auf das intuitive Vorhersageverhalten von Individuen in einer experimentellen Umgebung. Die Probanden haben die Aufgabe, zukünftige Werte der Inflation einer fiktiven Volkswirtschaft vorherzusagen. Dies geschieht, nachdem sie die historische Entwicklung des Bruttoinlandsprodukts und der Inflation entsprechender Volkswirtschaft in grafischer und tabellarischer Form erhalten haben. In 30 Perioden werden jeweils Vorhersagen über die Inflation in der nächsten Periode verlangt, wobei die Probanden entsprechend der Präzision ihrer Vorhersage bezahlt werden. Nach jeder Prognose erhalten sie ein Feedback. Während der Vorhersageperioden erfahren die Probanden einen ein-periodischen, nicht-vorhersehbaren Schock; die Simulation einer Extremsituation. In einem between-subjects-design wird ein positiver oder negativer Angebotsschock induziert. Die Ergebnisse zeigen, dass nur sehr wenige Probanden rationale Vorhersagen abgeben. Eher lassen sich die Prognosereihen anhand einfacher statistischer Regeln, sog. Heuristiken, beschreiben. 69 Prozent der Probanden wechseln ihre Vorhersageheuristik durch den Schock. Nach dem negativen Angebotsschock steigt die statistische Effizienz der Vorhersagen stark an. Nach dem positiven Schock ist dies allerdings nicht zu beobachten. Dies ist Evidenz für einen sog. negativity bias. Es zeigt sich also, dass makroökonomische Extremsituationen das Vorhersageverhalten von Experimentteilnehmern beeinflussen. Allerdings variieren die Effekte entsprechend der Charakteristika der Extremsituation.
Keywords: C91; D84; E03; 330; macroeconomic experiment; inflation expectations; intuitive forecasting; shocks; heterogeneity